2018
DOI: 10.36076/ppj.2018.3.295
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Radiofrequency Ablation for the Treatment of Glossopharyngeal Neuralgia Secondary to Oropharyngeal Carcinoma

Abstract: Background: The management of glossopharyngeal neuralgia due to oropharyngeal carcinoma is particularly difficult because of rich innervations of the area, erosive nature of neoplasm and dynamic pain evoked by the functional movements like swallowing and chewing. Few case reports have shown the efficacy of pulsed radiofrequency (PRF) treatment in primary and secondary glossopharyngeal neuralgia in non-cancer patients. However, the efficacy of PRF ablation of the glossopharyngeal nerve in oral cancer patients i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…We evaluated the therapeutic effects of PRF in patients with idiopathic GPN and the results revealed that PRF could obtain a promising effect with an effective rate of 93.3% at 1 month postoperatively with long-term recurrence-free survival rates of 54.8% at 120 months postoperatively. The short-term efficacy we observed is consistent with that of Bharti et al, 26 who reported a study about GPN secondary to oropharyngeal carcinoma that was treated by PRF. In their study, the treatment was effective in 23 out of 25 patients (92%), for more than 3 months without major complications.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We evaluated the therapeutic effects of PRF in patients with idiopathic GPN and the results revealed that PRF could obtain a promising effect with an effective rate of 93.3% at 1 month postoperatively with long-term recurrence-free survival rates of 54.8% at 120 months postoperatively. The short-term efficacy we observed is consistent with that of Bharti et al, 26 who reported a study about GPN secondary to oropharyngeal carcinoma that was treated by PRF. In their study, the treatment was effective in 23 out of 25 patients (92%), for more than 3 months without major complications.…”
Section: Discussionsupporting
confidence: 91%
“…In their study, the treatment was effective in 23 out of 25 patients (92%), for more than 3 months without major complications. However, Bharti et al 26 reported that the average duration of effective pain relief was only 5 to 9 months. As a result, we speculate that PRF can attain longer duration of pain relief for the treatment of idiopathic GPN than secondary GPN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, blocking the spinal ganglion can block the transmission of peripheral pain signals to the upper center, thereby inhibiting the release of excitatory transmitters and regulating changes in central plasticity. 16,17 In clinic, pulsed radiofrequency (PRF) of dorsal root ganglion (DRG) has been widely used in many diseases, such as knee osteoarthritis, 18,19 pubic neuralgia, 20 postherpetic neuralgia, 21 occipital neuralgia, 21 glossopharyngeal neuralgia, 22 etc, due to its advantages of less destructiveness, quick recovery, and obvious effect. 23 In recent years, the research on the mechanism of PRF has been carried out gradually.…”
Section: Discussionmentioning
confidence: 99%
“…After intensively reading the recent article "Pulsed Radiofrequency Ablation for the Treatment of Glossopharyngeal Neuralgia Secondary to Oropharyngeal Carcinoma" written by Bharti et al (1), we were so excited to see the conclusion they made about the efficacy of pulsed radiofrequency (PRF), but we are really confused about the parameters of PRF treatment that they used during the procedure.…”
Section: To the Editormentioning
confidence: 99%